Status and prospects of coal mining in Tuva - Dabiev, David F. (The New Research of Tuva, 2013)
Article considers into the coal resource base of Tuva. It shows the structure of coal mining in the republic and assesses the prospects of coking coal mining in Tuva. Influence of coal mining complex to the social and economic development of Republic of Tyva is studied.